Energy efficiency and thermal comfort: a case study in Iraqi Government Hospitals - Gatea, Anwer Abdulhussein (2023)
One of the largest energy consumers in the building sector are hospitals. In hospitals, many buildings tend to operate 24-hours daily throughout the year, among them are the wards, operation theatre and emergency department and hence require a balance between energy efficiency and thermal comfort among its occupants. The present work is a pioneering case study on energy efficiency and thermal comfort carried out at three hospitals in Iraq, designated as Hospital A, Hospital B, and Hospital C. The main objective of this study was to evaluate the present energy consumption, propose relevant active energy efficiency strategies and to evaluate thermal comfort among these Iraqi hospitals. The energy efficiency study includes walk-through and detailed energy audit while the thermal comfort study involves quantitative and qualitative measurements. From the energy audits, it was found that the average electricity consumed annually from 2016 to 2018 were 19,574,967 kWh, 12,100,426 kWh, and 4,317,093 kWh for Hospitals A, B, and C respectively with a corresponding building energy index (BEI) of 532, 484 and 260 kWh/m2/year. The energy consumption by the air conditioning system was between 62% to 65% for these hospitals, followed by lighting system consuming 17% and plug-loads at about 20%. The ambient temperature and the hospitals’-built area were found to be major factors affecting energy use. The proposals for energy efficiency result in potential energy savings of 16%, 15% and 12% for HVAC system and 14% to 21% for lighting system and plug-load for these hospitals. As for the thermal comfort study, the predicted mean vote (PMV) and predicted percentage of dissatisfaction (PPD) were evaluated based on ASHRAE Standard at 60 locations in the hospitals. A good relationship between predicted mean vote (PMV) and thermal sensation vote (TSV) was observed, with correlation coefficient, R2 of 0.69 from the linear regression analysis. It was also found that many slightly cooler than the acceptable thermal comfort range, indicating opportunities for energy efficiency in line with the proposed strategies.